2008
DOI: 10.1002/fuce.200700050
|View full text |Cite
|
Sign up to set email alerts
|

PEMFC Performance in a Magnetic Field

Abstract: A polymer electrolyte fuel cell is operated in a magnetic field gradient (B × dB/dx = ±3 T2�m–1) and the power output is investigated at lower partial pressure of oxygen gas and lower temperature than customarily used in fuel cells. The effects of the magnetic field are not confirmed at the cell current of i < 12 mA cm–2. On the other hand, the cell performance is improved or deteriorated depending on the direction of the magnetic field gradient at higher current densities at which the mass transfer of oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Later, Fukunaka et al loaded a gradient magnetic field on both the anode and cathode sides of PEMFC and found that the magnetic field affects the diffusion process of oxygen molecules rather than catalysis. It was the direction of the magnetic field and oxygen diffusion that determined the inhibition or promotion of battery performance . In fact, the battery performance improvement was related to the F K , and the enhancement mechanism is clarified in Section .…”
Section: Magnetic Field-enhanced Electrocatalysismentioning
confidence: 98%
See 1 more Smart Citation
“…Later, Fukunaka et al loaded a gradient magnetic field on both the anode and cathode sides of PEMFC and found that the magnetic field affects the diffusion process of oxygen molecules rather than catalysis. It was the direction of the magnetic field and oxygen diffusion that determined the inhibition or promotion of battery performance . In fact, the battery performance improvement was related to the F K , and the enhancement mechanism is clarified in Section .…”
Section: Magnetic Field-enhanced Electrocatalysismentioning
confidence: 98%
“…The mechanism is attributed to the attraction of paramagnetic oxygen by F K to achieve oxygen enrichment, avoiding the phenomenon of “congestion” of diamagnetic N 2 or H 2 O on the electrode surface and providing more channels for oxygen transmission. Of note is that the magnetic force can also increase the airflow velocity at the interface and promote the oxygen flow in the reaction zone, thereby improving the device performance. …”
Section: Possible Mechanisms Of Magnetic Field-enhanced Electrochemic...mentioning
confidence: 99%
“…37,38 The QSEI stabilizing effect can also be macroscopically boosted by an external magnetic field when magnetic oxides are involved. 39,40 Experiments demonstrate that the application of an external magnetic field can induce an overall improvement in the PEMFC catalytic performance, by accelerating the oxygen transport toward the catalytic layer of the electrodes 41 or activating the hydrogen molecules 42 or aligning proton-conductive channels in the fuel cell membrane. 43 In summary, exogenous and endogenous magnetic potentials must be unavoidably considered to achieve a comprehensive description of chemical, physical, and thus catalytic properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…One aspect that has not been explored intensively so far is the role of magnetism. There are very few studies that have connected the chemical bonding in heterogeneous interfaces of either the solid or gas phase , to magnetic properties, even though, magnetic field induced enhancement of ORR were observed experimentally. The observed results are usually explained in terms of convection within the diffusion layer which again depends on the gradient of the magnetic field and the concentration gradient of the paramagnetic oxygen species . It should be noted that the results obtained in the present work do not require an applied magnetic field to have nonzero gradient and are valid in uniform magnetic fields.…”
Section: Introductionmentioning
confidence: 56%